The Influence of Leadership and Human Resource Management on Employee Performance at the Housing, Settlement Areas, and Environmental Office of Sibolga City - Dharma Wangsa, Sheha Mutiah Syah; Ambarita, Rosmita; Sihite, Tiurlina Hasmawati (Journal of Economics, Management and Accounting (JEMA), 2026)
This study aims to determine whether there is an influence of leadership and human resource management on employee performance at the Housing, Settlement Areas, and Environmental Office of Sibolga City. This research uses an associative causal research design with quantitative data presentation. The population consisted of 439 employees, and the sample was determined as 15% of the total population, resulting in 66 respondents. The data were analyzed using the multiple linear regression analysis method with the assistance of the SPSS data processing application. The results of the study indicate that the correlation between the leadership variable and the human resource management variable with the employee performance variable obtained values of 0.753 and 0.699, which are categorized as very strong and strong correlations. The coefficient of determination shows that leadership and human resource management simultaneously influence employee performance by 64.7%. Furthermore, the t-test results show significant values of 5.588 for leadership and 4.089 for human resource management, where these values are greater than the t-table value of 1.998. Therefore, since t-count > t-table, it can be concluded that the variables of leadership and human resource management have a positive and significant partial effect on employee performance.